First report for Massaria disease on plane trees in Bulgaria - Mihaela Hristova; Margarita Georgieva; Maxim Yanev; Blagoy Koychev (Silva Balcanica)
Massaria disease caused by the fungal pathogen Splanchnonema platani (anamorph Macrodiplodiopsis dermazieresii) was found for the first time in the winter of 2023 on fallen branches of plane trees (Platanus × acerifolia) in park ‘Rupite’, southwestern Bulgaria. In 2023-2024, the symptoms of the disease were found on the fallen branches of ornamental trees in green city areas of Yambol, Gabrovo, Stara Zagora and Sofia. The life cycle of the Massaria disease was studied in the period June, 2023 – June, 2024 on plane trees planted in the Arboretum of Forest Research Institute in Sofia. Conidia of the anamorph state Macrodiplodiopsis dermazieresii were observed during the entire year, while the ascospores of the telemorph state Splanchnonema platani was reported in February to April 2023-2024. This study was the first report of Massaria disease on Platanus × acerifolia in Bulgaria.